Comparison of Antibiofilm Activities of Green Coffee Beans (Coffea Canephora P.) and Roasted Robusta Coffee (Coffea Canephora L.) Against Staphylococcus Aureus ATCC 25923 - Wicahyo, Septian Maulid; Wardani, Tatiana Siska; Erikania, Susanti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Biofilm is a collection of microbial cells that are irreversibly attached to a surface and encased in an EPS matrix (Extracellular Polymeric Substances). One of the infectious bacteria that produce biofilms is Staphylococcus aureus. Coffee contains compounds that are responsible for antibacterial activity, including alkaloids, flavonoids, phenolics, terpenoids/steroids and saponins among others. The purpose of this study was to determine the activity of the antibiofilm between Green Coffee (Coffea canephora P.) and Robusta Coffee (Coffea canephora L.) against Staphylococcus aureus bacteria. Extraction of green coffee beans and robusta coffee beans was carried out by maceration method, fractionation was carried out by liquid-liquid extraction method using water, ethyl acetate and n-hexane as solvents. Inhibitory activity and biofilm degradation were carried out using the crystal violet staining method which was read at a wavelength of 595 nm. Obtained inhibition and degradation were analyzed using the ANOVA statistical test. The method for testing anti-biofilm activity was determined by testing the inhibition of biofilm formation and biofilm degradation using extracts and fractions robusta green coffee bean (Coffea canephora P.) and roasted robusta coffee beans (Coffea canephora L.) at various concentrations of 2, 4, 8 and 16 mg/ml. Robusta roasted coffee bean extract has the greatest anti-biofilm inhibition effectiveness with IC50 biofilm inhibition of 2.13 ppm. The ethyl acetate fraction from roasted robusta coffee beans has the greatest effectiveness in destroying (degrading) anti-biofilms with the EC50 biofilm degradation of 1.93 ppm.